DRIVERS OF AUDITORS’ INCLINATION TOWARDS ACCOUNTABILITY AND TRANSPARENCY IN THE NIGERIAN PUBLIC SECTOR (Journal of Global Accounting, 2025)
The issues of accountability and transparency have been a major focus in the enthronement of sound public finance management (PFM) globally. Given the inconsistencies in the Nigerian PFM system and expected role vested on auditors internally and externally, this study examines determinants of auditors’ proclivity towards evidential accountability and transparency. The study relies on cross-sectional survey design achievable via close-ended questionnaire to collect data. The responses of 302 auditors across Federal and Kwara State ministries, departments and agencies are analysed using PLS-SEM to test the study’s five hypotheses formulated. It is found that all the identified factors except auditees’ behaviour positively explain Nigerian public sector auditors’ inclination towards accountability and transparency. However, among the factors with positive impact, audit facilities, external and the regulatory and institutional reform factors are superior given their statistical significant coefficients. These findings emphasise that to institutionalise accountability and transparency through public sector audit, huge investments have to be made in the 21st century audit facilities, all-inclusive global best practices in public sector audit should be adopted and there should be rare political class unholy influence in the audit process in Nigeria. However, the auditors’ inclination towards accountability and transparency in Nigeria stands to be unceasingly unsatisfactory until unfavourable human resource and auditees’ behaviour angles as established are attended to by concerned stakeholders. The contribution of this study to the relevant literature can be inferred from its focus on enthroning accountability and transparency in the polity via sound public sector audit which is a vital ingredient of sound PFM. Conversely, the fact that the study’s respondents are domicile in a State despite being employees of both Federal and State governments provides avenue for further studies with the focus on a geo-political zone or the country at large.
Keywords: Accountability; Audit Facilities; Human Resource Factors; Public Sector Auditors; Political Influence; Regulatory Reforms.